Individual differences in rumination in healthy and depressive samples: association with brain structure, functional connectivity and depression. Issue 14 (29th July 2015) - Wang, K.; Wei, D.; Yang, J.; Xie, P.; Hao, X.; Qiu, J.
Abstract : Background: Rumination is an important cognitive risk factor for onset and relapse of depression. However, no studies have employed a dimensional approach in investigating the neural correlates of rumination and the relationship with depression. Method: Non-clinical healthy subjects ( n = 306), who completed the classical rumination and depression scales, were studied using voxel-based morphometry and regional homogeneity (ReHo). Subsequently, mediation analysis was conducted to examine the influence of rumination on the relationship between brain structure and depression. Moreover, depressive patients ( n = 60) and a control group ( n = 63) of comparable age and education were studied with regions of interest that were identified in the healthy individuals. Results: For healthy individuals, regional grey-matter volume (rGMV) of dorsolateral prefrontal cortex (DLPFC) and parahippocampal gyrus (PHG) were positively correlated with rumination. In addition, rumination had a mediating effect on the relationship between the DLPFC and PHG and depression. Moreover, ReHo analysis showed that rumination had a significantly negative correlation with functional homogeneity of DLPFC. However, compared to the control group, depressed patients showed significant decrease of rGMV in the DLPFC and PHG and there was a significant negative correlation between DLPFC volume and depressive rumination. Conclusions: Increased DLPFC volume (decreased ReHo) in healthy individuals while decreased in depression indicated the trend of DLPFC from inefficient inhibition ('overload state') to impaired regulatory mechanism ('paralysis state'). This finding might elucidate when and why healthy individuals would develop sustained negative mood and depression eventually.